2014
DOI: 10.1175/jamc-d-13-041.1
|View full text |Cite
|
Sign up to set email alerts
|

MLS and CALIOP Cloud Ice Measurements in the Upper Troposphere: A Constraint from Microwave on Cloud Microphysics

Abstract: . Because the microphysics assumption is critical in satellite cloud ice retrievals, the agreement found in the IWC-b 532 relationships increase fidelity of the assumptions used by the lidar and microwave techniques for upper-tropospheric clouds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…At all altitudes CALIOP seems to underestimate the IWC with respect to CloudSat. Wu et al (2014) show that the V3 CALIOP IWC agrees well with airborne in situ measurements up to approx. 20 mg m −3 at an altitude of 12 km.…”
Section: Output Data: Cirrus Properties From Caliopsupporting
confidence: 61%
“…At all altitudes CALIOP seems to underestimate the IWC with respect to CloudSat. Wu et al (2014) show that the V3 CALIOP IWC agrees well with airborne in situ measurements up to approx. 20 mg m −3 at an altitude of 12 km.…”
Section: Output Data: Cirrus Properties From Caliopsupporting
confidence: 61%
“…The PSD of McFarquhar and Heymsfield (1997) was selected both for this study and by Millán et al (2013). Recent results in Wu et al (2014) indicate that this PSD is less realistic than what is assumed in the CloudSat retrievals, at least for altitudes around 15 km.…”
Section: Discussionmentioning
confidence: 99%
“…Avery et al . [] looked at CALIOP, MLS, and CloudSat cloud ice retrievals and concluded that MLS and CloudSat underreported small ice crystals relative to CALIOP, and MLS ice water content retrievals are quite noisy at high altitudes [also see Wu et al ., ]. HIRDLS and CALIOP data are the most relevant observational data sets for this study since they have better vertical coverage and are sensitive to small particles.…”
Section: Model Description and Data Usedmentioning
confidence: 99%